The Correlation Between Breakfast Habits and Physical Activity with the Nutritional Status of Adolescents at UPT SMP Negeri 25 Gresik - Nabila Firdausi; Annas Buanasita; Inne Soesanti; Mujayanto Mujayanto (Journal of Nutrition Explorations, 2025)
The high prevalence of poor breakfast habits and low physical activity among adolescents in Gresik, which exceeds national and provincial rates, highlights a nutritional concern requiring further investigation. This cross-sectional study involved 52 randomly selected eighth-grade students at UPT SMP Negeri 25 Gresik. Data on breakfast habits, physical activity, and nutritional status were collected through interviews and anthropometric measurements, then analyzed using the Chi-square test with SPSS. Results showed that 75% had good breakfast habits and 90.4% engaged in light physical activity. Nutritional status indicated 40.4% had normal weight, 38.5% were overweight, 7.7% were obese, and 15.4% were undernourished. There was no significant relationship between breakfast habits and nutritional status (p = 0.084), but physical activity showed a significant association with nutritional status (p = 0.043), confirmed by Fisher’s Exact Test (p = 0.008). In conclusion, physical activity was significantly associated with nutritional status, while breakfast habits were not. Schools and parents should promote regular physical activity and healthy eating to support adolescent health and prevent overweight and obesity.